Numerical Simulation of Bed Level Changes Around Structure Due to Waves and Current - Nurdjaman, Susanna; Putra, Prayoga Aryandi (Jurnal Teknik Sipil, 2017)
AbstractInteractions between sediments in the marine environment with the dynamics of the ocean can generate sediment movement. Sedimentation and erosion is the result of these interactions, which often have a negative impact on the harbor waters or coastal environment. The purpose of this research is to understand the process of sediment transport caused by the dynamics of currents and waves on the basis of morphological changes and the potential that can lead to scour for coastal protection structures (groin).Coupled model of hydrodynamic model, spectral wave and sediment transport were conducted to study the pattern of sediment movement. Simulations carried out by varying the waveform specification that propagates to the domain model. Verification of maximum velocity magnitude due to Van Rijn (1987), Nurdjaman and Ningsih (2003), and Adilantip (2012) shows good agreement with the differences value below 5%. While verification of wave height and wave stress radiation with analytical calculation shows good comparison with the mean of differences value 15%. The results of the study indicate that scour depth of 0,955 m was formed at the end of the simulation by the discharge input only. When the discharge combined with the various wave height and periods, scour depth increases by about 3 - 14%. Location of the scour depth coincides with the location of the maximum velocity at the tip of the groin structures to the left side.AbstrakInteraksi antara sedimen di lingkungan laut dengan dinamika laut dapat menghasilkan pergerakan sedimen. Proses sedimentasi dan erosi merupakan hasil dari interaksi tersebut yang tak jarang berdampak negatif terhadap perairan pelabuhan ataupun lingkungan pesisir. Tujuan dari penelitian ini yaitu untuk memahami proses transpor sedimen yang diakibatkan oleh dinamika arus dan gelombang terhadap perubahan morfologi dasar dan potensinya yang dapat mengakibatkan gerusan terhadap struktur pelindung pantai (groin). Dilakukan model kopel hidrodinamika, gelombang spektral, dan transpor sedimen untuk mempelajari pola pergerakan sedimen. Simulasi dilakukan dengan memvariasikan perbedaan spesifikasi gelombang yang menjalar terhadap domain model. Simulasi dilakukan dengan memvariasikan spesifikasi waveform yang merambat ke model domain. Verifikasi besarnya kecepatan aliran maksimum dari hasil model oleh Van Rijn (1987), Nurdjaman dan Ningsih (2003), dan Adilantip (2012) menunjukkan kesesuaian yang baik dengan perbedaan nilai di bawah 5%. Sedangkan verifikasi tinggi gelombang dan radiasi tegangan gelombang dengan perhitungan analitik menunjukkan perbandingan yang baik dengan rata-rata perbedaan nilai 15%. Hasil penelitian menunjukkan bahwa kedalaman gerusan 0,955 m terbentuk pada akhir simulasi dengan input debit sungai saja. Bila ddebit sungai dikombinasikan dengan berbagai tinggi dan perioda gelombang, kedalaman gerusan meningkat sekitar 3 - 14%. Lokasi kedalaman gerusan bertepatan dengan lokasi kecepatan aliran maksimum pada ujung struktur groin sisi kiri.